Salvianolate Ameliorates Osteopenia and Improves Bone Quality in Prednisone-Treated Rheumatoid Arthritis Rats by Regulating RANKL/RANK/OPG Signaling - Xiang Gao; Xiang Gao; Qingyun Wu; Qingyun Wu; Xinle Zhang; Jia Tian; Dahong Liang; Yalin Min; Jiaqi Lu; Xuemei Zhang; Liao Cui; Bilian Xu; et al. (Frontiers Media S.A., 2021)
Rheumatoid arthritis (RA) is closely associated with periarticular osteopenia and leads to a high risk of generalized osteoporosis. Although glucocorticoid (GC) treatment ameliorates joint degradation and manages inflammation in RA, GC application may induce further bone quality deterioration in RA patients. Current treatments for RA lack relevant strategies for the prevention and treatment of osteopenia in RA. In this study, we aimed to investigate whether salvianolate treatment ameliorated osteopenia in prednisone-treated RA rats. Lewis rats with collagen-induced arthritis (CIA) were administered prednisone (PDN) or PDN plus salvianolate (PDN+Sal) treatment for 90 days. The effects of Sal were investigated in PDN-treated CIA rats. To further evaluate the effects of Sal under inflammatory conditions, we investigated the effects of Sal treatment on the TNF-α-induced inflammatory response in MC3T3-E1 osteoblasts. Bone histomorphometry, bone mineral density (BMD), bone biomechanical properties, micro-computed tomography (micro-CT), immunohistochemistry, RT-PCR and western blot analyses were performed to evaluate the effects of Sal. The results demonstrated that RA induced bone loss and bone quality deterioration, with high bone turnover in CIA rats. PDN+Sal treatment significantly increased BMD and trabecular/cortical bone mass, suppressed inflammation, and improved bone biomechanical properties compared to CIA control and PDN treatment. PDN+Sal treatment significantly suppressed bone resorption and the RANKL and RANKL/OPG ratios compared to PDN. PDN+Sal and PDN treatment significantly inhibited TNF-α by 82 and 83%, respectively, and both suppressed inflammation in CIA rats. However, there was no significant difference between PDN+Sal and PDN treatment alone in regard to bone formation parameters or the management of inflammation and arthropathy. Sal significantly increased Osterix, OPN, and Col1a1 while decreasing RANKL, TRAF6, and TRAIL gene in TNF-α-induced MC3T3-E1 osteoblasts. Sal significantly increased Osterix, OPN and RUNX2 while decreasing NF-κB, TRAF6 and IL-1β protein in TNF-α-induced MC3T3-E1 osteoblasts. The results suggested that salvianolate treatment ameliorated osteopenia and improved bone quality in prednisone-treated RA rats, and the potential mechanism may be related to the regulation of the RANKL/RANK/OPG signaling pathway, TRAIL-TRAF6-NFκB signal axis, and downregulation of inflammatory cytokines. Salvianolate could be used as a promising supplemental therapeutic strategy to ameliorate osteopenia and improve bone quality in GC-treated RA patients.